The Effect of Digital Literacy on Readiness for Digital Change with Resistance to Change as a Mediating Variable (A Study of Civil Servants at the Ministry of Communications and Digital Technology's Human Resource Development Agency) - Shera Mayangsari suwito; Pantius Drahen Soeling (Green Publisher Indonesia, 2026)
This study aims to analyze the effect of digital literacy on readiness for digital change, both directly and indirectly through resistance to change as a mediating variable, among Aparatur Sipil Negara (ASN) at the Badan Pengembangan Sumber Daya Manusia (BPSDM) of the Kementerian Komunikasi dan Digital (Kemkomdigi). The study employed a quantitative approach with an explanatory, cross-sectional design. Data were collected through a 5-point Likert-scale online questionnaire administered to 282 ASN respondents from BPSDM, selected using a proportional quota sampling technique from a population of 945 ASN across 15 work units. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. The results showed that digital literacy had a positive and significant effect on readiness for digital change (β = 0.226; p = 0.001), digital literacy had a negative and significant effect on resistance to change (β = −0.605; p < 0.001), and resistance to change had a negative and significant effect on readiness for digital change (β = −0.568; p < 0.001). In addition, resistance to change was found to partially mediate the relationship between digital literacy and readiness for digital change, with an indirect effect (β = 0.344) greater than the direct effect. These findings confirm that enhancing ASN readiness for digital change depends not only on strengthening digital competencies but also on organizational efforts to manage employees' psychological resistance to change.